Visualization-Based Discovery of Vanin-1 Inhibitors for Colitis - Wang, Guankai; Wang, Jingjing; Du, Lupei; Li, Minyong (Frontiers in Chemistry, 2022)
The main effect of Vanin-1/VNN1 is related to its pantetheinase sulfhydrylase activity, which can hydrolyze pantetheine into pantothenic acid and cysteamine. In recent studies, the enzymatic activity of vanin-1/VNN1 has been found to be essential in the development of many diseases. The study of specific vanin-1/VNN1 inhibitors can give us a deeper understanding of its role in the disease process. In this study, different skeletal inhibitors were designed and synthesized using pyrimidine amide compounds as lead compounds. In order to screen inhibitors intuitively, a fluorescent probe PA-AFC for in vitro evaluation of inhibitors was designed and synthesized in this study, which has good sensitivity and specificity. The bioluminescent probe PA-AL was then used for cellular level and in vivo inhibitor evaluation. This screening method was convenient, economical and highly accurate. Finally, these inhibitors were applied to a mouse colitis model, confirming that vanin-1 is useful in IBD and providing a new therapeutic direction.